The Influence of Preformed HLA Class I and II Panel Reactive Antibodies on Clinical and Pathological Outcomes of Kidney Allograft - (:unkn) unknown (TURK NEFROLOJI DIYALIZ TRANSPLANTASYON DERGISI, 2016)
OBJECTIVE: The aim of the study was to investigate the influence of preformed anti-HLA antibodies that are represented by peak PRA levels on clinical and histopathologic outcomes of kidney allograft. MATERIAL and METHODS: The study was a retrospective cohort that consisted of 111 kidney transplant recipients. A peak PRA level greater than 15% was accepted positive for HLA class I and II antibodies. Flow cytometric assay was used for PRA and lymphocyte cross-match (LCM). All recipients were LCM negative. Allograft biopsies were indication biopsy and evaluated according to Banff 2011 criteria to investigate the influence of HLA antibodies. RESULTS: PRA was positive in 21.5% of patients for Class-I and 22.5% for Class-II antibodies. PRA Class-II positive patients had significantly more graft failure (p=0.028), death censored graft failure (p=0.008), acute rejection (p=0.016) and chronic rejection (p=0.029). Regarding the pathological evaluation, peritubular capillaritis score was significantly higher in PRA Class-II positive patients (0.44 +/- 0.78 vs. 1.55 +/- 1.12, p=0.008) and more patients had a glomerulitis+peritubular capillaritis score >= 2 (64% vs. 36%, p=0.026). These significant clinical and pathological outcomes were not observed for PRA Class-I and PRA Class I+II positive patients. CONCLUSION: Preformed anti-HLA Class-II antibodies are responsible for increased allograft rejection and reduced graft survival despite the negative flow cytometric lymphocyte crossmatch in kidney transplantation.
Keywords: Kidney transplantation; Panel reactive antibody; Flow cytometry; DONOR-SPECIFIC ANTIBODIES; RENAL-TRANSPLANTATION; CROSS-MATCHES; GRAFT FAILURE; RISK; RECIPIENTS